(untitled) (World Bulletin of Public Health, 2022)
The aim of our study was to study the results of surgical treatment of patients with cavity formations of the liver with its different anatomical location. The results of surgical treatment were analyzed in 37 patients with cavity liver formations. Of these, 26 patients of group I were with cavity formations in the I-IV segments of the liver, which does not require great technical difficulty during the operation, associated with its anatomical location. Group II of the study included 11 patients with cavitary liver lesions with complex anatomical locations of the liver, in which the lesions were located in the VII and VIII segments of the posterior clique of the diaphragm, which caused great technical difficulties in performing the operation due to the difficulty of access to the lesion